Governance, institutional change and regional development - Danson, Mike; Halkier, Henry; Cameron, Greta (Aldershot, Hampshire, England ; Brookfield, Vt. : Ashgate Pub. Ltd., 2000)
This volume addresses the prominent role given to institution-building, institutional change and governance in regional development strategies and policies. Central to the discussions presented here are the question of governance, and the consequences of new modes of governance
Includes bibliographical references and index
rpm 24/08/16
Loans
Keywords: Regional planning; Regionalism; Public-private sector cooperation; European union countries